2012
DOI: 10.1002/chem.201201339
|View full text |Cite
|
Sign up to set email alerts
|

Protonation‐Assisted Conjugate Addition of Axially Chiral Enolates: Asymmetric Synthesis of Multisubstituted β‐Lactams from α‐Amino Acids

Abstract: β-Lactams with contiguous tetra- and trisubstituted carbon centers were prepared in a highly enantioselective manner through 4-exo-trig cyclization of axially chiral enolates generated from readily available α-amino acids. Use of a weak base (metal carbonate) in a protic solvent (EtOH) is the key to the smooth production of β-lactams. Use of the weak base is expected to generate the axially chiral enolates in a very low concentration, which undergo intramolecular conjugate addition without suffering intermolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…The strategy for intramolecular conjugate addition via MOC has been applied to asymmetric β-lactam synthesis. 53 The major issue with this reaction was to avoid retro-Michael reaction from the highly strained intermediary βlactam enolate (Scheme 23). Use of a weaker base, such as Cs 2 CO 3 , and a protic solvent, such as EtOH, were found to be the key to the smooth formation of the desired β-lactams.…”
Section: Scheme 20 Intermolecular Aldol Reactions Via Mocmentioning
confidence: 99%
“…The strategy for intramolecular conjugate addition via MOC has been applied to asymmetric β-lactam synthesis. 53 The major issue with this reaction was to avoid retro-Michael reaction from the highly strained intermediary βlactam enolate (Scheme 23). Use of a weaker base, such as Cs 2 CO 3 , and a protic solvent, such as EtOH, were found to be the key to the smooth formation of the desired β-lactams.…”
Section: Scheme 20 Intermolecular Aldol Reactions Via Mocmentioning
confidence: 99%
“…The configuration of the highly substituted b-amino acids that were obtained was established through an alternative synthesis and by X-ray structure determination. The possibility of incorporating different groups at position 2 of the b-amino acid is open because azetidinones with different substituents at C-3 have been described, [21] and could be used as precursors for new 2-oxoazepane derivatives. Because the alkylation at position 1 of the 2-oxoazepane seems plausible, the possible preparation of different N-substituted-piperidine-containing b 2,3,3amino acids could also be anticipated.…”
Section: Resultsmentioning
confidence: 99%
“…[16] To understand the excellent stereochemical outcome,w e performed additional experiments with model substrate 3' ' (Scheme 5a), which consists of aUV-absorbing chromophore that allows for facile reaction analysis.When we analyzed the remaining aldol substrate in the incomplete reaction mixture, it was found that the proline stereocenter was not racemized (see the Supporting Information). These results confirmed that MOC was exerted during the intramolecular aldol reaction of 3.The virtually complete retention of chirality obtained in the polar protic solvent is remarkable considering the prior observations in which the competitive protonation of the enolate decreased the enantioselectivities of the MOC reactions in protic solvents.…”
Section: Methodsmentioning
confidence: 99%
“…These results confirmed that MOC was exerted during the intramolecular aldol reaction of 3.The virtually complete retention of chirality obtained in the polar protic solvent is remarkable considering the prior observations in which the competitive protonation of the enolate decreased the enantioselectivities of the MOC reactions in protic solvents. [16] To understand the excellent stereochemical outcome,w e performed additional experiments with model substrate 3' ' (Scheme 5a), which consists of aUV-absorbing chromophore that allows for facile reaction analysis.When we analyzed the remaining aldol substrate in the incomplete reaction mixture, it was found that the proline stereocenter was not racemized (see the Supporting Information). Additionally,the hydrogen at the proline stereocenter was gradually replaced with deuterium when the aldol reaction was conducted in EtOD (Scheme 5a;f or details,s ee the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%